N‐Type Rigid Semiconducting Polymers Bearing Oligo(Ethylene Glycol) Side Chains for High‐Performance Organic Electrochemical Transistors. (12th March 2021) - Chen, Xingxing; Marks, Adam; Paulsen, Bryan D.; Wu, Ruiheng; Rashid, Reem B.; Chen, Hu; Alsufyani, Maryam; Rivnay, Jonathan; McCulloch, Iain
Abstract: N‐type conjugated polymers as the semiconducting component of organic electrochemical transistors (OECTs) are still undeveloped with respect to their p‐type counterparts. Herein, we report two rigid n‐type conjugated polymers bearing oligo(ethylene glycol) (OEG) side chains, PgNaN and PgNgN, which demonstrated an essentially torsion‐free π‐conjugated backbone. The planarity and electron‐deficient rigid structures enable the resulting polymers to achieve high electron mobility in an OECT device of up to the 10 −3  cm 2  V −1  s −1 range, with a deep‐lying LUMO energy level lower than −4.0 eV. Prominently, the polymers exhibited a high device performance with a maximum dimensionally normalized transconductance of 0.212 S cm −1 and the product of charge‐carrier mobility μ and volumetric capacitance C* of 0.662±0.113 F cm −1  V −1  s −1, which are among the highest in n‐type conjugated polymers reported to date. Moreover, the polymers are synthesized via a metal‐free aldol‐condensation polymerization, which is beneficial to their application in bioelectronics. Abstract : Two new n ‐type semiconducting polymers, PgNaN and PgNgN, bearing oligo(ethylene glycol) (OEG) side chain are developed with a fully conformationally locked backbone and deep‐lying LUMO energy level. As a result, the polymer of PgNaN exhibits a good performance on OECT devices with a maximum dimensionally normalized transconductance of 0.212 S cm −1 and a product μC * of 0.662±0.113 F cm −1  V −1  s −1 .